Serum levels of immune globulins in postmaturity. Issue 3 (March 1974) - Papadatos, C.; Alexiou, D.; Papaevangelou, G.; Petropoulos, H.; Mendris, J.
Abstract : Immunoglobulins G, A, and M were measured in the serum of 32 term and 59 postmature newborns and their respective mothers. Duration of pregnancy was judged by calculated gestational age, placental pathological findings, and clinically recognizable signs of postmaturity. IgA levels were higher and IgG levels were lower in postmature babies and their respective mothers than in term newborns and their mothers. IgM levels were similar in the two groups studied.